Smart Reader Al-Quran Sensor / Muhammad Fauzan Hazim Mohd Nazri - Mohd Nazri, Muhammad Fauzan Hazim (2020)
The product that my company created is Smart Al-Quran Reader Sensor. This product is suitable for all kind generation Muslim person. This product also suitable for non-muslim person for who try to learn about Al- Quran, Hadith, Sirah and more about Islam. This is because person who do not know how to read Al-Quran and want to learn about Islam will easy learn with this product. Why did I say it was suitable? This is because the product comes with many materials, for example Digital Al.Quran, Sirah book, Hadith book, Tafsir, pen reader and many more. Customers who do not know how to read and want to learn just put the pen reader point at the Digital Al-Quran and other materials. This pen reader will emit sound the content of the Digital Al-Quran and the other materials. If they do not know, they will learn a lot there. There are many companies that have produced this product that are similar to our product but we have already created some differences in this product that other companies do not have. We improve by placing sound sensors on our products that other companies do not have. The customer or reader can challenge or test themselves to recite Al-Quran. The sensor will detect the reader's voice when they recite the Al-Quran. If they read the Quran wrongly, the pen will give a signal that the reader is misreading. Thus, they can evaluate their reading level.